2010
DOI: 10.1111/j.1470-6431.2010.00908.x
|View full text |Cite
|
Sign up to set email alerts
|

‘I send the wife to the doctor’– Men's behaviour as health consumers

Abstract: This paper explores men's behaviour and attitudes in relation to health matters. While there has been some practical and research progress in engaging with users of health services, there is less development in the area of engaging non-users. In effect, all members of the society can be the consumers/users of health promotion, though not all are. This paper reports on the first stage of a wider project aimed at increasing the effectiveness of skin cancer awareness messages aimed at men. The project focuses on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 51 publications
1
28
0
Order By: Relevance
“…Conformity to masculine gender role norms and perceived gender differences in health appeared to be important barriers to men's help‐seeking, which is consistent with the wider health‐related help‐seeking literature . A considerable number of men indicated that masculine gender role norms influence decisions to seek help for medical symptoms.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Conformity to masculine gender role norms and perceived gender differences in health appeared to be important barriers to men's help‐seeking, which is consistent with the wider health‐related help‐seeking literature . A considerable number of men indicated that masculine gender role norms influence decisions to seek help for medical symptoms.…”
Section: Discussionsupporting
confidence: 74%
“…Moreover, some men reported a previous negative experience with the healthcare system , or a low level of previous contact with the system . Financial cost was a barrier in one study .…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…an individual who suffers intense pain, but doesn't show it). Several investigations have suggested that measuring this construct could be useful in certain clinical contexts (Buckley & Ó Tuama, 2010;George & Fleming, 2004;Moore, Grime, Campbell, & Richardson, 2013;Murray et al, 2008;O'Brien, Hunt, & Hart, 2005;Yong, 2006). Hence, better characterization of stoical patients would enable more efficacious strategies to be designed for interventions such as decision-making in oncology.…”
Section: Introductionmentioning
confidence: 99%
“…Gender, race/ethnicity, marital status, and health behaviors will influence use of CAM. Females in general tend to be more interested in health and nutrition issues (Nayga, ), are more likely to engage in health‐seeking behavior (Buckley & Tuama, ), and are more frequent users of CAM than males (Montalto et al., ; Wellman, Kelner & Wigdor, ). In this study, women are hypothesized to be more likely than men to use CAM.…”
Section: Model Of Demand For Healthmentioning
confidence: 99%